A nanotubular NiCo-LDHs-based photoanode loaded with PSII and a preparation method thereof
Patent Information
- Application Number
- CN202610984234.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-07-03
AI Technical Summary
[0005]然而,现有的PSII基半人工光合作用体系仍面临一些问题
本方法以PSII为核心组装基元,采用纤维素滤纸作为牺牲模板,成功构筑了纳米管状结构的NiCo-LDHs载体材料(简记为T-NiCo),并通过静电组装构建了NiCo-LDHs/PSII光阳极体系;本方法以滤纸为NiCo-LDHs材料合成模板,采用水热法与低温碱溶解过程相结合,显著降低实验门槛。
Smart Images

Figure CN122499845B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of bio-optoelectronic technology, and in particular to a photoanode based on nanotube NiCo-LDHs loaded with PSII and its preparation method. Background Technology
[0002] Photosystem II (PSII) is a core membrane protein complex responsible for photocatalytic water splitting and oxygen release in natural photosynthesis. As the only biocatalyst in nature capable of efficiently driving water splitting under mild conditions, PSII possesses unique light-harvesting, charge-separation, and water-oxidizing capabilities. Under illumination, it can convert light energy into chemical energy while releasing oxygen, protons, and electrons. This characteristic makes it an ideal biofunctional unit for constructing semi-artificial photosynthesis systems. By coupling with artificial functional materials, directional electron transport chains can be reconstructed in vitro, achieving efficient conversion of solar energy into electrical or chemical energy, demonstrating significant application potential in the fields of new energy conversion and solar energy utilization.
[0003] However, natural PSII molecules face several inherent limitations in in vitro applications. First, while PSII exhibits strong absorption of red-orange and blue-violet light, it absorbs weakly in the green light region, which accounts for a large proportion of solar energy, thus limiting its light energy utilization efficiency. Second, the electron transport process of PSII relies on the natural microenvironment of the thylakoid membrane to maintain its conformation and function, exhibiting strict spatial orientation. If separated from the natural membrane structure, PSII proteins are prone to conformational changes, leading to decreased structural stability and rapid decline in photocatalytic activity. Furthermore, the low interfacial electron transport efficiency and high charge transfer resistance between PSII and electrodes severely restrict its practical application in photoelectric conversion systems.
[0004] To address the aforementioned issues, various bio-semi-artificial photoelectric conversion strategies based on functional material modification have been developed. For example, PSII is composited with inorganic semiconductor nanomaterials (such as metal oxides, perovskite quantum dots, and porous carbon-based materials), utilizing their tunable energy level structure and three-dimensional porous morphology to provide stable anchoring sites for PSII proteins and improve interfacial interactions. Introducing fluorescent dyes as light-harvesting antennas can effectively broaden the spectral absorption range of the system and compensate for PSII's insufficient absorption of green light. Composite conductive polymers help construct efficient electron transport channels, reducing charge transfer resistance between the protein and the electrode. Furthermore, researchers such as Li Junbo from the Institute of Chemistry, Chinese Academy of Sciences, proposed using molecular assembly technology to combine PSII with lipid membrane structures and polymer matrices to construct a semi-biological hybrid system that simulates the microenvironment of natural thylakoids, thereby improving the in vitro stability of the protein and maintaining its catalytic activity.
[0005] However, existing PSII-based semi-artificial photosynthesis systems still face some challenges. On the one hand, maintaining the long-term stability and activity of PSII after it leaves the natural membrane environment remains a key challenge; current material protection strategies are insufficient to completely inhibit in vitro protein inactivation, resulting in limited photoelectric conversion efficiency. On the other hand, the electron transport efficiency at the PSII protein-electrode interface needs further improvement, and the problem of high interfacial impedance has not been fundamentally resolved, hindering the development of PSII-based semi-artificial photosynthesis systems and their large-scale application in the energy sector. Summary of the Invention
[0006] The purpose of this application is to provide a photoanode based on nanotube NiCo-LDHs loaded with PSII and its preparation method, so as to solve or alleviate the problems existing in the prior art.
[0007] To achieve the above objectives, this application provides the following technical solution: Step 1: Prepare PSII diluent; Step 2: Using cellulose filter paper as a sacrificial template, nickel-cobalt layered bimetallic hydroxides—nanotube-shaped NiCo-LDHs—are constructed through a solvothermal reaction. Step 3: Prepare a T-NiCo dispersion solution by placing NiCo-LDHs in an ethanol aqueous solution; sequentially drop-coat the T-NiCo dispersion solution and PSII diluent onto a conductive substrate to obtain a NiCo-LDHs / PSII electrode.
[0008] LDHs consist of a brucite layer composed of divalent / trivalent cations, with anions and their water of crystallization existing between the layers. Due to the diversity of metal ions in the layers and the tunability of interlayer anions, LDHs possess tunable physicochemical properties. LDHs exhibit good biocompatibility, binding to biomolecules through electrostatic interactions or hydrogen bonds, providing a stable environment for proteins and thus helping to maintain their native structure and catalytic activity. Among various LDHs, NiCo-LDHs, due to the synergistic effect of Ni and Co, can broaden the spectral absorption range and adjust the optical band gap by adjusting the appropriate metal ratio, exhibiting excellent photocatalytic activity and electron transport capabilities, and have been widely studied in photocatalysis and electrocatalysis. Therefore, assembling NiCo-LDHs as a support material with PSII molecules can establish a highly efficient electron transport interface while maintaining protein activity, thereby improving its photoelectric conversion efficiency. Using cellulose filter paper as a sacrificial template, nanotube-shaped NiCo-LDHs were constructed from CoCl₂·6H₂O, NiCl₂·6H₂O, and CO(NH₂)₂ through a hydrothermal process and alkaline solution treatment. The cellulose surface contains abundant hydroxyl groups, which can attract hydrated metal ions (NiCl₂·6H₂O, NiCl₂·6H₂O, and CO(NH₂)₂) via electrostatic adsorption and hydrogen bonding. 2+ Co2+ The cellulose precursor is enriched on the surface of the fiber backbone, thus confining the nucleation and growth process of the metal precursor to the hierarchical fibrous structure of the filter paper fibers, gradually forming LDHs coated on the fibers, thereby achieving controllable adjustment of the material morphology; finally, the cellulose template is removed by an alkaline solution freezing process to form hollow tubular NiCo-LDHs. This hollow structure not only increases the specific surface area and protein loading capacity of LDHs, but also helps to improve the light absorption utilization rate and photoelectric properties of the system by utilizing the reflection of light inside the cavity; Furthermore, step one includes the following steps: Fresh spinach leaves were placed in the dark at 4°C overnight. Buffer A was added to a high-speed blender at a ratio of 200-300 mL per 100 g of leaves for blending. The mixture was filtered through 7-9 layers of gauze. The filtrate was centrifuged at 250-400 g for 0.5-2 min to remove the precipitate. The supernatant was then centrifuged at 5000-7000 rpm for 10-30 min. The supernatant was discarded, and the resulting precipitate was the chloroplast. Unless otherwise specified, this step and subsequent steps were performed at 4°C under green light protection. The chloroplast precipitate was resuspended and homogenized in buffer B, and magnetically stirred for 15-30 minutes to rupture the chloroplasts. The precipitate was then removed by centrifugation at 200-300g for 1.5-2.5 minutes. The resulting supernatant was centrifuged at 6000-8000g for 15-30 minutes. The resulting precipitate was the thylakoid membrane. The ratio of spinach leaves to buffer B was 40-60 mL of buffer B per 100 g of leaves. The thylakoid membrane was resuspended and homogenized using buffer C, and the chlorophyll concentration was measured by UV-Vis. The chlorophyll concentration of the system was adjusted to 2 mg / mL–3 mg / mL. Then, buffer D was prepared, consisting of 20 mM MES, 0.4 M sucrose, 15 mM NaCl, 5 mM MgCl2, and 20 wt% TX-100, with a pH of 6.5. Buffer D was slowly added to the resuspended and homogenized thylakoid membrane to ensure that the TX-100 and chlorophyll content were in a homogeneous mass ratio. The ratio of the two components is 17:1 to 23:1. After stirring slowly for 10 to 15 minutes, the mixture is centrifuged at 9000g to 11000g for 1 to 2 minutes. The precipitate is discarded, and the supernatant is centrifuged at 27000g to 30000g for 30 to 45 minutes to obtain the precipitate. The precipitate is washed with buffer C and centrifuged until the supernatant is colorless. The obtained precipitate is the PSII protein complex. The PSII protein complex is resuspended and homogenized with buffer E, and the chlorophyll concentration (Chl) is measured. The mixture is then aliquoted into 0.2 mL to 0.5 mL portions and frozen in liquid nitrogen.
[0009] Furthermore, in the nanotube-shaped NiCo-LDHs, the molar ratio of nickel to cobalt is 1:1 to 3:1.
[0010] Furthermore, the PSII content is expressed as chlorophyll concentration (Chl). In the NiCo-LDHs / PSII electrode, the mass ratio of PSII to NiCo-LDHs is 1:20 to 1:160; the loading of NiCo-LDHs on the conductive substrate per unit area is 2.0 mg / cm². 2 ~2.5mg / cm 2 .
[0011] Furthermore, step two includes the following steps: Filter paper A is obtained by washing and drying cellulose filter paper; Mixture A is prepared by dissolving nickel salt, cobalt salt, and urea in methanol; Filter paper A was placed in mixture A for a solvothermal reaction to obtain filter paper B loaded with NiCo-LDHs; Filter paper B was dissolved in an alkaline aqueous solution at low temperature to obtain a cellulose template solution; the cellulose template solution was subjected to solid-liquid separation, and the resulting solid was washed and dried to obtain nanotube-shaped NiCo-LDHs.
[0012] Furthermore, in step two, the temperature of the solvothermal reaction is 130℃~180℃, and the reaction time is 12h~18h.
[0013] Furthermore, in step three, the T-NiCo dispersion solution is drop-coated onto the conductive substrate in two stages. The second drop-coating is performed after the first T-NiCo dispersion solution has dried.
[0014] This application also proposes a photoanode based on nanotube-based NiCo-LDHs loaded with PSII, wherein the photoanode based on nanotube-based NiCo-LDHs loaded with PSII is prepared using the aforementioned preparation method.
[0015] Furthermore, the photoanode based on nanotube-shaped NiCo-LDHs loaded with PSII comprises: Conductive substrate; The T-NiCo functional layer, loaded on the surface of the conductive substrate, is composed of nanotube-shaped NiCo-LDHs; A PSII functional layer is loaded onto the surface of the T-NiCo functional layer; the PSII functional layer is formed by drop-coating and drying a PSII diluent.
[0016] The technical solution of this application has the following beneficial effects: This method uses PSII as the core assembly unit and cellulose filter paper as a sacrificial template to successfully construct a nanotubular NiCo-LDHs carrier material (abbreviated as T-NiCo), and then constructs a NiCo-LDHs / PSII photoanode system through electrostatic assembly. This method uses filter paper as a template for the synthesis of NiCo-LDHs materials and combines hydrothermal method with low-temperature alkaline dissolution process, which significantly reduces the experimental threshold.
[0017] The nanotube-shaped NiCo-LDHs (T-NiCo) in the photoanode of this application were prepared by the filter paper sacrificial template method. Both the inner and outer surfaces can be loaded with PSII, and the structure is a hierarchical structure similar to the stacked cavities of natural thylakoids, which greatly improves the interfacial assembly of PSII. The band structure of NiCo-LDHs (T-NiCo) matches that of PSII, forming a Z-shaped electron transport, which optimizes the electron transport path between the interfaces and promotes the separation of photogenerated electrons and holes, thereby effectively improving the photoelectric conversion efficiency of the system. The photoresponse signal of the formed photoanode system is higher than the sum of the carrier and PSII, indicating a synergistic effect. Attached Figure Description
[0018] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. Wherein: Figure 1 This is a schematic diagram of electron transport in the NiCo-LDHs / PSII assembly system.
[0019] Figure 2 The transient photocurrent curves and photocurrent curves under continuous illumination of the materials in the examples and control groups are shown below. Among them, (a) and (b) are the direct photocurrent curves and direct photocurrent densities of PSII 40μL, T-NiCo and T-NiCo / PSII electrodes with different PSII loadings, respectively; (c) is the direct photocurrent curve of PSII 40μL, T-NiCo and T-NiCo / PSII 40μL electrodes under continuous illumination; (d) and (e) are the indirect photocurrent curves and indirect photocurrent densities of PSII 40μL, T-NiCo and T-NiCo / PSII 40μL electrodes, respectively; and (f) is the indirect photocurrent curve of PSII 40μL, T-NiCo and T-NiCo / PSII 40μL electrodes under continuous illumination.
[0020] Figure 3The results show the direct and indirect photocurrent response tests of the electrodes of Example 1 and Control Group 2 under single-wavelength conditions. Among them, (a) and (b) are the direct photocurrent responses of the electrodes of Example 1 and Control Group 2 under different single wavelengths, respectively; (c) is the direct photocurrent density and photoelectric conversion efficiency of the electrodes of Example 1 and Control Group 2 under single wavelength; (d) and (e) are the indirect photocurrent responses of the electrodes of Example 1 and Control Group 2 under different single wavelengths, respectively; and (f) is the indirect photocurrent density and photoelectric conversion efficiency of the electrodes of Example 1 and Control Group 2 under single wavelength.
[0021] Figure 4 The images show the results of confocal laser scanning microscopy (CLSM) observations of the electrodes in Example 1; where (a), (b), and (c) are respectively the confocal laser scanning microscopy (CLSM) image of the electrodes in Example 1, the fluorescence image under 488nm laser excitation, and the fluorescence image under 561nm laser excitation.
[0022] Figure 5 The images show the SEM observation results of the electrodes of Example 1, Control Group 1, and Control Group 2; where (a) and (b) are SEM images of the electrode of Control Group 1, (c) and (d) are SEM images of the electrode of Control Group 2, and (e) and (f) are SEM images of the electrode of Example 1.
[0023] Figure 6 The images are SEM images of the materials prepared in the preliminary experiment; (a) and (b) are SEM images of T-Ni, (c) and (d) are SEM images of T-NiCo(3:1), (e) and (f) are SEM images of T-NiCo(2:1), (g) and (h) are SEM images of T-NiCo(1:1), (i) and (j) are SEM images of T-Co, and (k) and (l) are SEM images of P-NiCo(2:1).
[0024] Figure 7 The images are transmission electron microscope (TEM) images and high-resolution transmission electron microscope (HR-TEM) images of the materials in group 2 after ultrasonic dispersion in the preliminary experiment; where (a)-(d) are TEM images of the materials in group 2, (e) is the energy dispersive spectroscopy (EDS) surface scan elemental distribution of a single nanotube in the material, (f) is the selected area electron diffraction pattern of the material, and (g)-(i) are HR-TEM images of the material.
[0025] Figure 8The X-ray photoelectron spectroscopy (XPS) of group 2 and the photoluminescence (PL) spectra of materials in groups 2 and 4-6 are shown in the preliminary experiment. Among them, (a), (b), (c), (d), and (e) are the full XPS spectrum, C 1s high-resolution spectrum, O 1s high-resolution spectrum, Ni 2p high-resolution spectrum, and Co 2p high-resolution spectrum of T-NiCo(2:1), respectively, and (f) is the PL spectrum of T-NiCo(2:1), T-Co, T-Ni, and P-NiCo(2:1).
[0026] Figure 9 The results of transient photocurrent response tests of materials in groups 1-6 in the preliminary experiment are shown. Among them, (a) and (b) are the direct photocurrent curves and direct photocurrent densities of materials in groups 1-6, respectively; (c) is the direct photocurrent curve under continuous illumination of T-NiCo(2:1) and P-NiCo(2:1); (d) and (e) are the indirect photocurrent curves and indirect photocurrent densities of materials in groups 1-6, respectively; and (f) is the indirect photocurrent curve under continuous illumination of T-NiCo(2:1) and P-NiCo(2:1).
[0027] Figure 10 The results of cyclic voltammetry and AC impedance testing of materials in groups 1-6 in the preliminary experiment are shown. Among them, (a)-(d) are the cyclic voltammetry test results of T-NiCo(2:1), T-Co, T-Ni, and P-NiCo(2:1) at different scan rates, respectively; (e) is the linear fitting result of the difference between anode current and cathode current at each scan rate on the scan rate; and (f) is the AC impedance Nyquist plot of materials in groups 1-6.
[0028] Figure 11 The X-ray diffraction (XRD) patterns of materials in groups 1-3 and group 6 in the preliminary experiment are shown.
[0029] Figure 12 The UV-Vis diffuse reflectance spectra of T-NiCo(2:1) and P-NiCo(2:1) in the preliminary experiment are shown; where (a) and (b) are the UV-Vis diffuse reflectance spectra of T-NiCo(2:1) and P-NiCo(2:1), respectively.
[0030] Figure 13 The results show the zeta potential measurements of the T-NiCo dispersion and the PSII dilution.
[0031] Figure 14 This is the Fourier transform infrared (FT-IR) spectrum of the PSII molecule extracted in this application. Detailed Implementation
[0032] The present application will now be described in detail with reference to the accompanying drawings and embodiments. The various examples are provided by way of explanation and not for limitation of the present application.
[0033] Example 1 A method for preparing a photoanode based on nanotube-shaped NiCo-LDHs supported on PSII includes the following steps: Step 1: Extract the PSII protein complex from spinach leaves, including the following steps: (1) Remove the petioles and veins from the purchased fresh spinach, wash it with ultrapure water, and place it in the dark at 4℃ overnight. All subsequent steps are carried out at 4℃ and under green light protection. (2) Add 250g of leaves that have been left overnight and 500mL of buffer A into a blender for crushing, and filter it with 8 layers of gauze; (3) Centrifuge the obtained filtrate at 400g for 1min to remove the precipitate, centrifuge the supernatant at 6000rpm for 15min, discard the supernatant, and the obtained precipitate is the chloroplast; (4) The obtained chloroplast precipitate was resuspended and homogenized in 100 mL of buffer B, and then magnetically stirred for 15 min to rupture the chloroplasts. After stirring, the suspension was centrifuged at 250 g for 2 min; (5) After centrifugation, discard the precipitate and centrifuge the supernatant at 7000g for 15min. The precipitate obtained is the thylakoid membrane. (6) The thylakoid membrane was resuspended and homogenized using buffer C, and the chlorophyll concentration was measured by UV-Vis. The chlorophyll concentration of the system was adjusted to 2.5 mg Chl mL. -1 ; (7) Then slowly add buffer D to the above solution so that the ratio of TX-100 to chlorophyll content (w / w) is 20:1, and then slowly stir the solution for 10 min; (8) Centrifuge the stirred solution at 10000g for 1min, discard the precipitate, centrifuge the supernatant at 27000g for 30min to obtain the precipitate, wash the precipitate with buffer C and centrifuge until the supernatant is colorless; (9) The obtained PSII protein complex was suspended and homogenized with buffer E, and the chlorophyll concentration was measured. The mixture was then aliquoted into 0.3 mL portions and frozen in liquid nitrogen. Buffer A consists of 20 mM Tricine, 0.4 M sucrose, 40 mM NaCl, 2 mM MgCl2, 2 mM Vitamin C, and 0.2% BSA, pH=7.8; Buffer B consists of 20 mM Tricine, 10 mM NaCl, 5 mM MgCl2, and 0.2% BSA, pH=7.8; Buffer C consists of 20 mM MES, 0.4 M sucrose, 15 mM NaCl, and 5 mM MgCl2, pH=6.5; Buffer D consists of 20 mM MES, 0.4 M sucrose, 15 mM NaCl, 5 mM MgCl2, and 20 wt% TX-100, pH=6.5; Buffer E consists of 20 mM MES, 0.4 M sucrose, 15 mM NaCl, 5 mM MgCl2, and 0.5 M betaine, pH=6.5.
[0034] In step (8) above, compared to the 35,000g centrifugal force disclosed in the literature, this application optimizes the centrifugal force to 27,000g, and maintains low temperature, light protection, and buffer protection throughout the process, so that the PSII protein complex can still be effectively enriched and separated. Therefore, the extraction process of this application can be completed using a conventional benchtop high-speed refrigerated centrifuge, without the need for an ultracentrifuge or higher-configuration centrifuge equipment, which reduces the equipment threshold and implementation cost of the preparation process, and is conducive to the promotion and repeated implementation of this PSII-based photoanode preparation method.
[0035] Step 2: Preparation of nanotube-shaped NiCo-LDHs, including the following steps: (a) Cut the filter paper into pieces with a diameter of 4 cm, and ultrasonically clean it with deionized water and ethanol for 20 min each. After cleaning, dry it at 60℃ for 8 h to obtain filter paper A. The filter paper used is Hangzhou Shuangquan Wohua rapid quantitative filter paper, and the weight of a single filter paper is about 0.10 g. (b) Weigh 1.1885 g of NiCl2·6H2O, 0.5948 g of CoCl2·6H2O and 0.9 g of CO(NH2)2 according to a molar ratio of 2:1, dissolve them separately in 20 mL of methanol solution, stir magnetically at room temperature for 30 min until completely dissolved, mix the three together and stir for 30 min until homogeneous to obtain mixture A; (c) Place two dried filter papers A in the liner of the reactor, and then pour the mixture A with a total volume of about 60 mL into the liner of the reactor. React at 150 °C for 12 h. (d) Transfer the sample after the reaction is completed into a 10 mL centrifuge tube, centrifuge at 8000 rpm for 10 min to separate it, then wash it three times each with deionized water and ethanol, and dry it at 60℃ for 24 h after washing to obtain filter paper B. (e) Prepare 100 mL of NaOH-CO(NH2)2 aqueous solution according to the ratio of NaOH:CO(NH2)2:H2O=7g:12g:81mL. Stir magnetically until completely dissolved, then place it in a -12℃ refrigerator for 1 hour to pre-cool. Then place two filter papers B in it and freeze in the refrigerator for 12 hours to obtain sample M. (f) After freezing, the sample M was taken out and stirred in an ice-water bath for 2 hours to completely dissolve it and obtain the cellulose template solution. Then, the obtained cellulose template solution was placed in a centrifuge tube and centrifuged at 8000 rpm for 10 min using deionized water and ethanol respectively. The tube was washed 3 times each and then dried at 60℃ for 24 hours to obtain nanotube-shaped NiCo-LDHs.
[0036] Step 3: Constructing the NiCo-LDHs / PSII assembly system: A 5 mg / mL T-NiCo dispersion was prepared by dissolving NiCo-LDHs in an ethanol-water solution; the water:ethanol volume ratio in the ethanol-water solution was 9:1; the sample was prepared in a container with dimensions of 0.6 cm × 1.3 cm and a base area of 0.78 cm². 2 160 μL of 5 mg / mL T-NiCo dispersion solution was drop-coated twice onto a 1.1 mm thick ITO conductive substrate. After the first drop-coating was completed and dried at room temperature, the second drop-coating was performed. Then, 40 μL of 1 mg Chl mL was added. -1 A diluted PSII solution was drop-coated onto the surface, and the electrode was slowly purged with nitrogen at a rate of 200 mL to 400 mL / min for 1 h at 4 °C in the dark to promote solvent evaporation and prevent photo-induced deactivation. After drying, a NiCo-LDHs / PSII electrode, denoted as T-NiCo / PSII 40 μL, was obtained for subsequent photoelectric performance testing. In this embodiment, the mass ratio of PSII (based on chlorophyll Chl) to NiCo-LDHs in the electrode was 1:40.
[0037] The chlorophyll concentration (Chl) measurement step in the above process includes: Two 20 μL samples were taken and diluted to 10 mL and 20 mL respectively with 80% acetone solution. The samples were then diluted 500-fold and 1000-fold. After centrifugation at 2000 g for 2 min, the supernatant was collected for UV-Vis measurement. The characteristic absorbance values at 645 nm, 663 nm, and 720 nm were recorded. The chlorophyll concentration in the samples was calculated using the Arnon formula. ; in, Chlorophyll concentration, unit: mg / L -1 8.02 and 20.21 are calibration coefficients for the classic Arnon acetone method, in mg / L. -1 ; Diluent, diluted 500 times. =500, diluted 1000 times =1000, where A663, A645, and A720 represent the characteristic absorbance values of the sample at 663nm, 645nm, and 720nm, respectively. Subtracting A720 from the formula is to remove the background, which is light scattering caused by the turbidity of the sample.
[0038] The photoanode based on nanotube-shaped NiCo-LDHs loaded with PSII, prepared by the above method, comprises: ITO conductive substrate, with a bottom area of 0.78 cm². 2 The dimensions are 0.6cm × 1.3cm; A T-NiCo functional layer, loaded onto the surface of the ITO conductive substrate, is composed of nanotube-shaped NiCo-LDHs; the NiCo-LDHs loading per unit area is 5 mg / mL × 320 μL / 0.78 cm². 2 =2.05mg / cm 2 ; A PSII functional layer is loaded onto the surface of the T-NiCo functional layer; the PSII functional layer is composed of a chlorophyll concentration of 1 mg Chl mL. -1 The PSII dilution solution was drop-coated and dried to form the product.
[0039] Figure 1 This is a schematic diagram of electron transport in the NiCo-LDHs / PSII assembly system. Figure 13 A dispersion of T-NiCo (concentration approximately 3 mg / mL) -1 ) and a diluted solution of PSII (concentration approximately 0.5 mg Chl mL) -1 The zeta potential measurement results of T-NiCo show that the overall T-NiCo exhibits a positive charge, consistent with the layered structure of LDHs. Positively charged cations form the brucite layer, while anions and water of crystallization exist between the layers. PSII molecules, due to the negative charge of functional groups such as carboxyl groups in amino acids, assemble with the LDHs through electrostatic adsorption, forming a stable composite structure that provides the structural basis for subsequent interfacial charge transfer. The microstructure of NiCo-LDHs forms a hierarchical structure resembling stacked thylakoid cavities. Simultaneously, the carrier material and PSII undergo electrostatic assembly, optimizing the assembly interface and enhancing the interfacial contact between PSII and the electrode material. Under simulated solar excitation, PSII and NiCo-LDHs form a Z-shaped electron transport chain, improving electron-hole separation efficiency, promoting charge transfer, and reducing energy loss.
[0040] Figure 14 The FT-IR spectrum of PSII shows that the PSII molecule is visible at 3300 cm⁻¹. -1The broad and strong peaks correspond to the stretching vibrations of NH and OH, mainly originating from amino groups and bound water molecules in protein molecules; at 1630 cm⁻¹ -1 The characteristic peak can be attributed to the amide I band, mainly due to the C=O stretching vibration, which is an important characteristic peak of protein secondary structure; at 1054 cm⁻¹ -1 The characteristic peaks on the left and right correspond to PO3. 2- These peaks originate from phospholipid molecules or phosphate groups in PSII. The presence of these characteristic infrared peaks indicates that the typical functional groups in the PSII molecule remain intact, suggesting that the protein molecular structure was not damaged during extraction and preservation. Simultaneously, these carboxyl and phosphate groups also facilitate hydrogen bonding or electrostatic adsorption with T-NiCo, thereby enhancing interfacial stability.
[0041] Example 2 This embodiment is another implementation based on embodiment 1. The description of the same technical solutions as in embodiment 1 will be omitted, and only the technical solutions that are different from those in embodiment 1 will be described.
[0042] In this embodiment, only the 1 mg Chl mL from step three of Example 1 is used. -1 The amount of PSII dilution solution dropped was changed from 40 μL to 20 μL, while other steps remained unchanged. The prepared photoanode was designated as T-NiCo / PSII 20 μL, where the mass ratio of PSII (calculated as chlorophyll Chl) to NiCo-LDHs was 1:80.
[0043] Example 3 In this embodiment, only the 1 mg Chl mL from step three of Example 1 is used. -1 The amount of PSII diluent was changed from 40 μL to 10 μL, while other steps remained unchanged. The prepared electrode was denoted as T-NiCo / PSII 10 μL, where the mass ratio of PSII (calculated as chlorophyll Chl) to NiCo-LDHs was 1:160.
[0044] Example 4 In this embodiment, only the 1 mg Chl mL from step three of Example 1 is used. -1 The amount of PSII diluent was changed from 40 μL to 80 μL, while other steps remained unchanged. The prepared electrode was designated as T-NiCo / PSII 80 μL, where the mass ratio of PSII (calculated as chlorophyll Chl) to NiCo-LDHs was 1:20.
[0045] Control group 1 Compared to Example 1, this control group does not load PSII; that is, after step two in Example 1, the T-NiCo electrode is directly constructed, as follows: NiCo-LDHs were placed in an ethanol-water solution to prepare a 5 mg / mL T-NiCo dispersion solution; the water:ethanol volume ratio in the ethanol-water solution was 9:1; 160 μL of the 5 mg / mL T-NiCo dispersion solution was drop-coated twice on an ITO conductive substrate. After the first drop-coating was completed and dried at room temperature, the second drop-coating was performed to obtain the NiCo-LDHs electrode, denoted as T-NiCo.
[0046] Control group 2 In control group 2, after extracting the PSII protein complex according to step one of Example 1, PSII was directly loaded onto an ITO conductive substrate, as follows: 40 μL of 1 mg Chl mL -1 The PSII dilution was drop-coated onto the surface of an ITO conductive substrate and then slowly purged with nitrogen at 200 mL to 400 mL / min for 1 h at 4 °C in the dark to promote solvent evaporation and avoid photo-induced deactivation. After drying, a PSII electrode was obtained, denoted as PSII 40 μL.
[0047] The codes for the examples and control groups are summarized in Table 1.
[0048] Table 1. Codes for Example and Control Groups
[0049] To determine the optimal assembly of PSII with the T-NiCo support material, i.e., the optimal assembly effect achievable at the interface provided by the T-NiCo hierarchical microstructure, transient photocurrent curve tests and continuous illumination photocurrent curve tests were performed on the electrodes prepared in the above examples and control groups. The results are as follows: Figure 2 As shown in the figure, (a) and (b) are the direct photocurrent curves and direct photocurrent densities of PSII 40μL, T-NiCo and T-NiCo / PSII electrodes with different PSII loadings, respectively. (c) is the direct photocurrent curve of PSII 40μL, T-NiCo and T-NiCo / PSII 40μL electrodes under continuous illumination. (d) and (e) are the indirect photocurrent curves and indirect photocurrent densities of PSII 40μL, T-NiCo and T-NiCo / PSII 40μL electrodes, respectively. (f) is the indirect photocurrent curve of PSII 40μL, T-NiCo and T-NiCo / PSII 40μL electrodes under continuous illumination.
[0050] Depend on Figure 2 As shown in (a) and (b), when the PSII loading is 40 μL of diluent, the system exhibits the strongest direct photocurrent response, with a peak current density of approximately 0.24 μA cm⁻¹. -2And in the first five cycles, it was higher than that of the T-NiCo electrode (0.13 μA cm⁻¹). -2 ) and PSII 40μL electrode (0.03μA cm) -2 The sum of the current densities indicates that an appropriate PSII assembly amount helps the interface between the two to achieve sufficient contact and synergistic effect. However, too much or too little PSII assembly may restrict interfacial charge transport, hindering the separation of photogenerated electrons and holes. Figure 2 As shown in (c), after 800 s of illumination, the photocurrent of the T-NiCo / PSII 40 μL assembled electrode basically stabilized, while the photocurrent of the PSII 40 μL electrode continued to decrease. After 1200 s of illumination, the T-NiCo / PSII 40 μL electrode still exhibited the highest photocurrent response (approximately 0.08 μA cm⁻¹). -2 The value was significantly higher than that of the T-NiCo electrode (0.04 μA cm⁻¹). -2 ) and PSII 40μL electrode (0.02μA cm) -2 This, and still exceeding the sum of their current densities, further demonstrates the synergistic effect of interfacial coupling on the photoelectric performance and stability of the assembled system. Figure 2 In steps (d) and (e), the photoelectric properties of this system via indirect electron transfer were studied, with 2 mM DCBQ added to the electrolyte as an electron acceptor. In the 2000 s transient photocurrent response curve test, the initial photocurrent density of the T-NiCo / PSII 40 μL electrode was significantly higher than that of the T-NiCo electrode (3.02 μA cm⁻¹). -2 ) and PSII 40μL electrode (0.57μA cm) -2 The sum of these values reaches 18.85 μA cm. -2 It is a T-NiCo electrode (3.02 μA cm⁻¹). -2 It is 6.24 times that of the PSII 40μL electrode (0.57μA cm⁻¹), and is also 6.24 times that of the PSII 40μL electrode (0.57μA cm⁻¹). -2 It is 33.07 times that of the T-NiCo / PSII 40μL electrode. Although the T-NiCo / PSII 40μL electrode exhibits significant degradation in later cycles, its current density is 3.87μA cm⁻¹ on the final cycle. -2 It is still higher than that of the T-NiCo electrode (2.27 μA cm⁻¹). -2 ) and PSII 40μL electrode (0.27μA cm) -2 The current density of ) is greater than the sum of the current densities of the two. Figure 2Figure (f) shows that during long-term continuous illumination testing, the photocurrent response of the T-NiCo / PSII 40μL electrode was still much higher than that of the T-NiCo electrode and the PSII 40μL electrode. Although its photocurrent decreased more rapidly over time, it still retained about 3.13 μA cm⁻¹ after 3600 s of continuous illumination. -2 Higher than that of the T-NiCo electrode (1.63 μA cm⁻¹). -2 ) and PSII 40μL electrode (0.29μA cm) -2 The current density of ) is greater than the sum of the current densities of the two.
[0051] To further investigate the photocurrent response and photoelectric conversion efficiency of the electrodes under different wavelengths of light, direct and indirect photocurrent response tests were conducted on the T-NiCo / PSII 40μL electrode (Example 1) and the PSII 40μL electrode (Control Group 2) under single-wavelength conditions. (See attached figures.) Figure 3 . Figure 3 In the figure, (a) and (b) show the direct photocurrent response of the T-NiCo / PSII 40μL electrode and the PSII 40μL electrode at single wavelengths (435nm, 560nm, 670nm, and 700nm), respectively. Figure 3 In the figure, (c) represents the direct photocurrent density and photoelectric conversion efficiency of the T-NiCo / PSII 40μL electrode and the PSII 40μL electrode at a single wavelength. Figure 3 In the middle (d) and (e), the indirect photocurrent responses of the T-NiCo / PSII 40μL electrode and the PSII 40μL electrode are respectively at single wavelengths (435nm, 560nm, 670nm, and 700nm). Figure 3 In the figure, (f) represents the indirect photocurrent density and photoelectric conversion efficiency of the T-NiCo / PSII 40μL electrode and the PSII 40μL electrode at a single wavelength. Figure 3 The vertical axis IPCE represents the incident photon-current conversion efficiency. Figure 3 The results show that the electrode exhibits the strongest photocurrent response under illumination at wavelengths of 435 nm and 670 nm. In single-wavelength direct photocurrent measurements, the photocurrent density of the T-NiCo / PSII 40μL electrode at 435 nm is significantly higher than that of the PSII 40μL electrode, which is 12.22 nA / cm². -2 Significantly increased to 48.51 nA cm -2 The photocurrent density at 670 nm is 10.09 nA cm⁻¹. -2 Significantly increased to 30.30 nAcm -2This indicates that the assembly substrate constructed using hollow nanotube T-NiCo as a carrier can effectively improve the conversion efficiency of PSII in its intrinsic visible light characteristic absorption region, namely blue-violet and red-orange light, significantly enhancing the system's photoresponse capability. During single-wavelength indirect photocurrent testing, both the T-NiCo / PSII 40μL electrode and the PSII 40μL electrode exhibited the strongest photocurrent response under 670nm single-wavelength illumination, with the T-NiCo / PSII 40μL electrode reaching a photocurrent density as high as 5.88μA cm⁻¹. -2 Compared to the photocurrent density of a simple PSII 40μL electrode (0.14μA cm⁻¹), -2 The efficiency is about 40 times higher, indicating that in the presence of electron acceptors, the tubular stacked layer interface provided by T-NiCo can significantly promote the transport of PSII-generated electrons to the electrodes and improve the utilization efficiency of photogenerated electrons.
[0052] To verify whether T-NiCo and PSII were successfully assembled, the T-NiCo / PSII assembly system of the preferred embodiment 1 of this application was observed using a confocal laser scanning microscope (CLSM). The results are as follows: Figure 4 As shown in the figure, (a), (b), and (c) are the laser confocal image, fluorescence image under 488 nm laser excitation, and fluorescence image under 561 nm laser excitation of the 40 μL T-NiCo / PSII electrode, respectively. Under 488 nm laser excitation, PSII exhibits obvious green fluorescence, while under 561 nm laser excitation, obvious red fluorescence is observed. The fluorescence signal as a whole shows the same tubular distribution characteristics as NiCo-LDHs and is distributed along the material skeleton, indicating that PSII is not randomly aggregated but attached to the surface of the tubular structure of NiCo-LDHs. The consistency between the fluorescence signal distribution and the microstructure of the carrier proves the successful construction of the T-NiCo / PSII assembly system.
[0053] SEM observations were performed on the T-NiCo electrode (control group 1), the PSII 40μL electrode (control group 2), and the T-NiCo / PSII 40μL electrode (Example 1). The results are as follows: Figure 5 As shown in the figure, (a) and (b) are SEM images of the T-NiCo electrode, (c) and (d) are SEM images of the PSII 40μL electrode, and (e) and (f) are SEM images of the T-NiCo / PSII 40μL electrode. From Figure 5 In (a) and (b), obvious pores can be observed. This hierarchical structure is beneficial for increasing the specific surface area of the electrode, providing ample space for the interfacial assembly of PSII, and helping to enhance the interfacial contact between PSII molecules and the electrode. Figure 5As can be observed in (c) and (d), the surface of the individual 40μL PSII electrode is relatively flat and does not exhibit porous structure characteristics. However, from... Figure 5 As can be observed in (e) and (f), the morphology of the electrode after PSII assembly is different from that of the T-NiCo electrode. The original pores are filled and become smoother, and the surface is covered with a relatively uniform film structure. This fully demonstrates that PSII has formed an assembly layer on the surface of the T-NiCo carrier.
[0054] Preliminary experiment In the aforementioned examples and step two (b) of control group 1, NiCl2·6H2O and CoCl2·6H2O were weighed at a molar ratio of 2:1. This ratio was determined based on preliminary experiments, and the preliminary experimental groups were set as follows: Group 1: Step 2 (b) Weigh 1.3370g NiCl2·6H2O, 0.4461g CoCl2·6H2O and 0.9g CO(NH2)2 according to a molar ratio of 3:1; other steps are the same as Step 2 of Example 1; the prepared material is denoted as T-NiCo(3:1); Group 2: Step 2 (b) Weigh 1.1885g NiCl2·6H2O, 0.5948g CoCl2·6H2O and 0.9g CO(NH2)2 according to a molar ratio of 2:1; this is the final nickel-cobalt ratio determined in this application; the steps in this group are the same as step 2 of Example 1; the material prepared is denoted as T-NiCo(2:1); Group 3: Step 2 (b) Weigh 0.8913g NiCl2·6H2O, 0.8922g CoCl2·6H2O and 0.9g CO(NH2)2 according to a molar ratio of 1:1; other steps are the same as Step 2 of Example 1; the prepared material is denoted as T-NiCo(1:1); Group 4: In step 2(b), CoCl2·6H2O is not weighed; the other steps are the same as step 2 of Example 1; the material prepared is denoted as T-Ni; Group 5: NiCl2·6H2O is not weighed in step 2(b); other steps are the same as step 2 of Example 1; the prepared material is denoted as T-Co; Group 6: No filter paper template is placed, and steps (a), (e), and (f) in step two of Example 1 are not performed. Other steps are the same as in Example 1. The material prepared is denoted as P-NiCo(2:1).
[0055] Table 2. Codes and Explanations for Groups 1-6
[0056] To investigate whether the introduction of the cellulose structural template and the subsequent template removal process affect the crystal structure of the material, P-NiCo(2:1) without using cellulose filter paper as a template was prepared in group 6. The XRD patterns are shown below. Figure 11 As shown in the figure, the position, shape, and full width at half maximum (FWHM) of the P-NiCo(2:1) diffraction peaks are not significantly different from those of T-NiCo(2:1), indicating that the alkaline solution removal of the template did not affect the crystal structure of the material.
[0057] The surface morphology of the materials prepared in groups 1-6 was observed using scanning electron microscopy. SEM images are shown below. Figure 6 As shown in the figure, (a) and (b) are SEM images of T-Ni, (c) and (d) are SEM images of T-NiCo(3:1), (e) and (f) are SEM images of T-NiCo(2:1), (g) and (h) are SEM images of T-NiCo(1:1), (i) and (j) are SEM images of T-Co, and (k) and (l) are SEM images of P-NiCo(2:1). In the figure, materials with different nickel-cobalt ratios prepared using cellulose filter paper as a template successfully replicated the hierarchical fiber structure of the template, and a stacked structure formed by cross-linking of nanosheets was observed in all cases. However, as the cobalt content in the precursor increased, the nanosheet size became larger and thicker, and the fiber structure gradually unfolded or even disappeared. Compared with T-NiCo(2:1), P-NiCo(2:1) material with the same nickel-cobalt ratio but without using a cellulose template exhibited a nanoflower-like structure. Therefore, NiCo-LDHs synthesized using cellulose filter paper as a template have a hierarchical microstructure with stacked cavities, which is expected to increase the specific surface area of the material, enhance the light absorption rate, increase the number of catalytic active sites, and thus improve the photoelectric performance.
[0058] Figure 7 The images show TEM and HR-TEM images of T-NiCo(2:1) (Group 2) material after ultrasonic dispersion. Figure 7 The TEM images (a)-(d) clearly show that the material is a nanotube structure formed by cross-linking of nanosheets, with a diameter of approximately 800 nm. Figure 7 (e) shows the EDS surface scan elemental distribution of a single nanotube in the material, clearly demonstrating the distribution characteristics of C, O, Co, and Ni. These elements exhibit a highly uniform distribution within the tube wall structure of T-NiCo(2:1), with no obvious elemental separation, indicating that the metal ions (Co) are well-distributed. 2+ Ni 2+ Uniform growth was achieved during the reaction process, and a homogeneous LDH structure was successfully constructed. Figure 7(f) in the figure is the selected area electron diffraction pattern of the material. Three concentric circles can be observed in the figure, indicating that the material has a polycrystalline structure. Figure 7 (g)-(i) are HR-TEM images of the material, showing clear lattice fringes. The measured interplanar spacings are 0.256 nm and 0.762 nm, corresponding to the (221) and (003) crystal planes of NiCo-LDHs, respectively, consistent with the XRD results. Figure 11 The above results show that NiCo-LDHs can maintain a stable nanotube structure after ultrasonic dispersion, and its unique hierarchical microstructure and uniform elemental distribution lay the structural foundation for its potential catalytic applications.
[0059] Figure 12 (a) and (b) in the figure are the UV-Vis DRS (diffuse reflectance spectra) of T-NiCo(2:1) and P-NiCo(2:1), respectively. Both T-NiCo(2:1) and P-NiCo(2:1) exhibit wide-range visible light absorption characteristics, indicating that NiCo-LDHs have good light absorption capabilities. Furthermore, the absorption peaks of the two are similar in shape, suggesting that using filter paper fiber as a sacrificial template mainly affects the microstructure of the material, but does not affect its intrinsic electronic structure. Figure 8 The figures show the X-ray photoelectron spectroscopy (XPS) of T-NiCo(2:1) and the photoluminescence (PL) spectra of T-NiCo(2:1), P-NiCo(2:1), T-Ni, and T-Co. (a), (b), (c), (d), and (e) are the full XPS spectrum, C 1s high-resolution spectrum, O 1s high-resolution spectrum, Ni 2p high-resolution spectrum, and Co 2p high-resolution spectrum of T-NiCo(2:1), respectively. (f) shows the PL spectra of different samples. As can be seen from the figures, compared to the single emission peaks of the single-metal samples T-Ni and T-Co, T-NiCo(2:1) and P-NiCo(2:1) exhibit two distinct emission peaks at 443 nm and 469 nm, indicating that the bimetallic components synergistically regulate the electronic structure and defect distribution of the material. The peak splitting indicates the existence of different types of defect energy levels or metal-oxygen charge transfer channels, consistent with the complex bandgap characteristics observed in UV-Vis absorption spectroscopy. Figure 12 Meanwhile, the luminescence intensity of T-NiCo(2:1) is significantly stronger than that of other materials, which may be due to the increased number of surface defects introduced by the sacrificial template or the formation of shallow energy level luminescence centers.
[0060] Figure 9The results of transient photocurrent response tests on materials in groups 1-6 are shown in the figure. (a) is the direct photocurrent curve of materials in groups 1-6, (b) is the direct photocurrent density of materials in groups 1-6, (c) is the direct photocurrent curve under continuous illumination of P-NiCo(2:1) and T-NiCo(2:1), (d) is the indirect photocurrent curve of materials in groups 1-6, (e) is the indirect photocurrent density of materials in groups 1-6, and (f) is the indirect photocurrent curve under continuous illumination of P-NiCo(2:1) and T-NiCo(2:1). Figure 9 As shown in (a) and (b), T-NiCo(2:1) exhibits the strongest direct photocurrent response, with a peak current density of approximately 0.11 μA / cm². -2 T-Ni exhibits the best photoelectric properties, while T-Ni shows the weakest photocurrent response. Similarly, compared to P-NiCo(2:1) without a filter paper cellulose template, T-NiCo(2:1) also shows significantly enhanced photoelectric properties, thanks to its hollow nanotubes and the hierarchical microstructure formed by their overlapping layers, which provides more active sites. Figure 9 As shown in (c), after 1200 s of illumination, the photocurrent density of T-NiCo(2:1) still reaches 0.043 μA cm⁻¹. -2 This is much higher than the photocurrent density of P-NiCo(2:1) (0.013 μA cm⁻¹). -2 This indicates that the introduction of the layered microstructure of filter paper cellulose into NiCo-LDHs significantly enhances the photoelectric properties and stability of the material. To further investigate the effect of electron transport processes on the photocurrent response, 2 mM 2,6-dichloro-1,4-benzoquinone (DCBQ) was added to the electrolyte as an artificial electron acceptor, and indirect photocurrent measurements were performed on the material (see...). Figure 9 (d) and (f) in the figure. DCBQ can rapidly capture and reduce photogenerated electrons, thereby effectively suppressing electron-hole recombination and accelerating the electron extraction process. In indirect photocurrent curve testing (see...),... Figure 9 In (d), it was found that samples with different nickel-cobalt ratios showed significantly improved photocurrent response in the electrolyte with added DCBQ. Among them, T-NiCo(2:1) still showed the strongest photocurrent response, with a peak current density of approximately 2.15 μA cm⁻¹. -2 The response was approximately 19.5 times higher than that of direct photocurrent. This result indicates that, without the addition of an electron acceptor, the electron transport process somewhat limits the photocurrent output of the system. However, with the introduction of an electron acceptor (DCBQ), electrons are rapidly transferred, reducing the recombination probability and allowing more holes to participate in the catalytic oxidation of water. Furthermore, T-NiCo(2:1) and P-NiCo(2:1) were also subjected to continuous illumination for 3600 s (see...). Figure 9In (f), it was found that the photocurrent density of T-NiCo(2:1) could still reach 1.34 μA cm⁻¹ after illumination. -2 The photocurrent density is higher than that of P-NiCo(2:1) (0.76 μA cm⁻¹). -2 This further demonstrates its significant advantages in electron transmission efficiency and stability.
[0061] To evaluate the electrochemical active area (ECSA) of the material, cyclic voltammetry tests were performed at different scan rates in the non-Radaic region (-0.059V~0.041V vs. NHE). The results are shown in [Figure number missing]. Figure 10 (a)-(d) are shown in the figures. No significant Faraday reaction occurs within this potential range; the current mainly originates from the charging and discharging process of the double layer. As the scan rate increases, the area under the CV curve also increases, indicating typical capacitive behavior of the material. The difference between the anolyte and cathode currents (Δj / 2) at each scan rate is linearly fitted to the scan rate, as shown in the figure. Figure 10 The slope obtained from (e) is the double-layer capacitance (C). dl C dl Proportional to the ECSA of the electrode, C dl The larger the value, the larger the ECSA, therefore it can be obtained through C. dl The size of the surface area is used to indirectly assess the electrochemical active area of the material. According to C... dl The ECSA values were estimated to be much higher than those of T-NiCo(2:1), T-Co, and P-NiCo(2:1), being 3.26 times that of T-Ni, 4.13 times that of T-Co, and 4.76 times that of P-NiCo(2:1), respectively. The larger ECSA indicates that it has more electrochemical active sites.
[0062] The charge transfer kinetics of water oxidation at the interface between the photoanode material and the electrolyte under illumination were studied using electrochemical impedance spectroscopy (EIS). Figure 10 (f) shows the Nyquist plots of different groups, which exhibit typical semi-circular arc characteristics, indicating that interfacial charge transfer dominates the kinetic characteristics of the catalytic water oxidation reaction, and that Faraday charge transfer is the main rate-limiting step.
[0063] To further analyze the interface charge transfer characteristics, an equivalent circuit diagram was used to fit the impedance data. The equivalent circuit mainly includes the series resistance (R). s ), charge transfer resistance (R) ct ) and constant phase element (CPE). Where R s The ohmic resistance of the system mainly originates from the resistance of the ITO conductive substrate, the contact resistance between the electrode and the substrate, and the ionic resistance of the electrolyte solution; R ctThe charge transfer resistance corresponding to the water oxidation process at the photoanode-electrolyte interface can be obtained from the diameter of the semicircle of the Nyquist curve; CPE is used to characterize the non-ideal capacitive behavior of the interface. Electrochemical impedance spectroscopy was fitted using Zview software, and the R values for each sample were found to be... s The small difference indicates good contact between the electrode and the conductive substrate, resulting in a low overall ohmic impedance, which is beneficial for electron transport to the external circuit. As can be seen from the Nyquist plot, the diameter of the semicircle represents R. ct The smaller the diameter of the semicircle, the greater the size of R. ct The lower the value, the better. Among them, T-NiCo(2:1) has the smallest semicircular diameter, exhibiting the lowest R value. ct The resistance value (1141Ω) indicates that the charge transport resistance at the interface between the electrode material and the electrolyte is minimal, resulting in a faster charge transfer process.
[0064] In summary, NiCo-LDHs (T-NiCo) effectively replicate the hierarchical microstructure of filter paper fiber templates, and a suitable metal ratio (Ni:Co = 2:1) significantly optimizes the physicochemical and photoelectric properties of NiCo-LDHs (T-NiCo). Their stable structural characteristics and excellent electron transport properties provide a superior carrier material for the assembly of PSII protein molecules. Therefore, T-NiCo (2:1) was used as the protein carrier material in the assembly process of the PSII-based photoelectric conversion system in this application.
[0065] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for preparing a photoanode based on nanotube-shaped NiCo-LDHs supported on PSII, characterized in that, Includes the following steps: Step 1: Prepare PSII diluent; Step 2: Using cellulose filter paper as a sacrificial template, nickel-cobalt layered bimetallic hydroxides—nanotube-shaped NiCo-LDHs—are constructed via a solvothermal reaction; the preparation of the NiCo-LDHs includes the following steps: Filter paper A is obtained by washing and drying cellulose filter paper; Mixture A is prepared by dissolving nickel salt, cobalt salt, and urea in methanol; Filter paper A was placed in mixture A for a solvothermal reaction to obtain filter paper B loaded with NiCo-LDHs; Cellulose template solution was obtained by dissolving filter paper B using an alkaline aqueous solution at low temperature. The cellulose template solution was subjected to solid-liquid separation, and the resulting solid was washed and dried to obtain nanotube-shaped NiCo-LDHs; The NiCo-LDHs have a hierarchical microstructure with stacked cavities; Step 3: NiCo-LDHs are placed in an ethanol-water solution to prepare a T-NiCo dispersion solution; the T-NiCo dispersion solution and PSII dilution solution are sequentially drop-coated onto a conductive substrate to obtain a NiCo-LDHs / PSII electrode; in this electrode, NiCo-LDHs and PSII are combined through electrostatic adsorption, and the band structure of NiCo-LDHs is matched with that of PSII to form a Z-type electron transport structure.
2. The method for preparing a photoanode based on nanotube-shaped NiCo-LDHs supported on PSII according to claim 1, characterized in that: In the nanotube-shaped NiCo-LDHs, the molar ratio of nickel to cobalt is 1:1 to 3:
1.
3. The method for preparing a photoanode based on nanotube-shaped NiCo-LDHs supported on PSII according to claim 1, characterized in that: The PSII content is expressed as chlorophyll concentration Chl. In the NiCo-LDHs / PSII electrode, the mass ratio of PSII to NiCo-LDHs is 1:20 to 1:
160.
4. The method for preparing a photoanode based on nanotube-shaped NiCo-LDHs supported on PSII according to claim 1, characterized in that: The loading of NiCo-LDHs on a conductive substrate per unit area is 2.0 mg / cm². 2 ~2.5mg / cm 2 .
5. The method for preparing a photoanode based on nanotube-shaped NiCo-LDHs supported on PSII according to claim 1, characterized in that: In step two, the temperature of the solvothermal reaction is 130℃~180℃, and the reaction time is 12h~18h.
6. The method for preparing a photoanode based on nanotube-shaped NiCo-LDHs supported on PSII according to claim 1, characterized in that: In step three, the T-NiCo dispersion solution is drop-coated onto the conductive substrate in two stages. The second drop-coating is performed after the first T-NiCo dispersion solution has dried.
7. A photoanode based on nanotubular NiCo-LDHs supported on PSII, characterized in that, The photoanode based on nanotube NiCo-LDHs loaded with PSII is prepared using the preparation method described in any one of claims 1 to 6.
8. The photoanode based on nanotube-shaped NiCo-LDHs supported on PSII according to claim 7, characterized in that, The photoanode based on nanotube-shaped NiCo-LDHs loaded with PSII includes: Conductive substrate; The T-NiCo functional layer, loaded on the surface of the conductive substrate, is composed of NiCo-LDHs stacked with nanotube cavities; A PSII functional layer is loaded onto the surface of the T-NiCo functional layer; the PSII functional layer is formed by drop-coating and drying a PSII diluent.
Citation Information
Patent Citations
Preparation of nickel-cobalt layered double hydroxide nanoparticle-supported bismuth vanadate compound material and application of nickel-cobalt layered double hydroxide-supported bismuth vanadate compound material to photoelectric water oxidation
CN109569630A